2 min read Jun 17, 2024

Simplifying Exponents: (x^3)^3 = x^n

In mathematics, understanding exponent rules is crucial for simplifying expressions and solving equations. One common rule involves raising a power to another power, like in the expression (x^3)^3 = x^n. Let's break down how to determine the value of 'n'.

Understanding the Rule

The rule for simplifying expressions of this form is: (x^m)^n = x^(m*n). This means that when raising a power to another power, we multiply the exponents together.

Applying the Rule

In our example, (x^3)^3, we have m = 3 and n = 3. Applying the rule, we get:

(x^3)^3 = x^(3*3) = x^9

Therefore, n = 9.


Let's consider another example: (y^2)^5 = y^n.

  • Applying the rule: (y^2)^5 = y^(2*5) = y^10
  • Therefore, n = 10.


Understanding this rule is essential for various mathematical operations, including:

  • Simplifying algebraic expressions
  • Solving exponential equations
  • Working with scientific notation

By consistently applying the rule, you can efficiently simplify complex expressions involving exponents and solve a wider range of mathematical problems.

Related Post

Featured Posts